Analysis of the rights and duties of insurers in Nigeria - Anifalaje, K. (University of Ibadan Law Journal, 2018)
The paper analyses the rights and duties of Nigerian insurers at common law emanating from the contractual relationship between the insurer and the insured as amplified or abridged under the statute. It argues that the statutory incursion into the common law rules of uberrimae fidei, insurable interest, conditions and warranties and assignment of policies, circumscribing some of the rights exercisable by the insurer against the insured to defeat just claims as well as expanding the scope of the insurer’s duties in order to improve on service delivery is salutary. The paper, however, concludes that further reform measures, aimed at addressing some other salient issues, are still essential in the overall interest of the insuring public.
Keywords: Assurances; Assureur; Common law; Duties; Insurers; Nigeria; Rights; Statute

The fairness of forfeiture clauses in short-term insurance contracts - Huneberg, Samantha (University of Johannesburg, 2018)
Insurance fraud is a major issue in the insurance industry. Insurance companies around the world are all facing significant losses due to the prevalence of fraudulent claims. These fraudulent claims and subsequent losses suffered by insurers inevitably lead to a dilution of the insurance pool and result in other policyholders bearing the brunt of these losses. The inevitable solution for insurers is to hike the premiums for all other policyholders in order to compensate for their losses caused by fraudulent claims. Insurance fraud is an international problem and it is common for insurers in most jurisdictions to use forfeiture clauses. These clauses aim to protect the insurer by stating that if the policyholder should submit any type pf fraudulent claim, the policyholder will forfeit the entire claim. There has been much controversy around the validity and fairness of these clauses. This thesis seeks to provide an overview of the prevalence of fraudulent insurance claims in South Africa, England, Australia and New Zealand. Moreover, it will consider the fairness of forfeiture clauses in light of the fundamental movement towards policyholder protection in recent years both in South Africa and in those jurisdictions that form part of the comparative study. The thesis concludes that forfeiture clauses form an indispensable part of short-term insurance contracts and are justifiable and therefore lawful. It is, however, submitted that insurance companies have a duty to disclose the nature and extent of forfeiture clauses at the inception of the policy and again at claim stage. By using so-called staggered disclosure, insurers provide policyholders with the opportunity to consider their claim and the means with which to prove it in order to avoid instituting a fraudulent claim. The thesis recommends that these rules pertaining to staggered disclosure should form part of the 2018 Policyholder Protection Rules, together with a statutory definition of insurance fraud.
Keywords: Forfeiture; Insurance policies; South Africa

Governing activities in outer space: responsibility, liability, regulation and the role of insurers - Harrington, Andrea (McGill University, 2017)
As we have seen from the numerous high profile launch failures and accidents that have occurred between 2014 and 2016, space activities are still ultra-hazardous in nature, despite sixty-plus years of technological development. These activities range from essential to modern life (ex., telecommunications) to futuristic and forward thinking (ex., space tourism). In order for these activities to not only continue, but also develop and grow, this inherent risk must be managed.Further complicating the risk dynamic in outer space, States are required to take liability and responsibility for the activities of their nationals in space, including private entities and individuals. The reality of this relationship is that while States wish to promote the development of their domestic space industries, they will also usually require certain levels of insurance and indemnification to protect the State against potentially costly mishaps.With regard to outer space, political will is lacking at an international level to create new binding rules for activities in space. Likewise, States are reluctant to unilaterally impose stricter (even if ultimately beneficial) regulations on their entities for fear that their domestic industries will flee abroad to greener pastures, creating a regulatory prisoner's dilemma. These factors create a scenario where the major space insurers responsible for writing policies across national boundaries may be uniquely positioned to enforce or at least promote mechanisms to increase safety and sustainability in the commercial space industry. Increasing safety and sustainability in outer space may help to keep premium costs from growing out of control for these hazardous activities, as well. Thus, this thesis addresses three fundamental questions: 1)From a legal and policy perspective, is there a regulatory void that needs to be filled, at least temporarily?2)Are insurance companies in a position to be able to fill or partially fill that void?3)If so, how, and what actions can they undertake to improve their ability to execute that governance function?In answering these questions, this manuscript-based thesis explores the existing body of space law and common practices in space activities, including notable lacunae, and applies theories of "insurance as governance." This approach permits both analysis of the existing status of the industry and recommendations to increase the viability of space activities moving forward.
Keywords: Air and Space Law; Droit des assurances; Insurance law; Insurers; Liability insurance; Liability insurer; Responsability

Cession of Life Insurance Policies in securitatem debiti : a Practical Perspective - Sunkel, Kelly (University of Pretoria, 2013)
The security cession of the rights under life policies marries two separate areas of the law: The Law of cession and the Law of Insurance. This makes for a complex union since varying common law and statutory principles find application, and in reality trade practices also play a role. In theory a cession in securitatem debiti may take one of two possible constructions, namely a pledge or a fiduciary security cession, and each has its own advantages and disadvantages. Disparity arose when judicial preference was given to the pledge construction while academics preferred the other. The problem, however, was larger than a disagreement as to the better construction. The underlying problem was that there was a lack regarding clarity as to the practical operation of security cession of life policies, in addition to the problems surrounding the construction thereof. As a solution to this problem some academics have suggested legislative intervention. The South African Law Reform Commission, nevertheless, advised against it in 1991 and was of the opinion that the issue was one which our courts would eventually solve. In the 22 years since then, our courts have merely confirmed its preference for the pledge construction. The intricacies of security cessions of life policies have seen no further judicial development. It is probable that the courts do not have enough practical information at hand to advance this area of the law. An investigation into the operation of such cessions in practice was thus necessary. The outcome of the practical investigation reveals that legislative intervention is indeed a viable solution especially since the issues are too complex for the courts to solve. As part of this work, legislation has been drafted and it is recommended that this is inserted into the Security by Means of Movable Property Act .
Keywords: Life Insurance; Security Cession